ENERGI SOSIAL DI PEDESAAN DALAM MEMBERDAYAKAN PEMBANGUNAN DI DESA (Forum Ilmu Sosial, 2016)
In the simplicity of village life, embodied energy that can move the social dynamics of local development. Social energy that grow and develop in the rhythm of village life. Present at very strong by being bound by the order of local values ? ? in the form of kinship, cultural values ? ? and local leadership. Therefore, it is very interesting from this study is how to mobilize social energy in rural development dynamics of rural communities. Set in northern remote villages in three districts in Pacitan, namely districts Donorojo, sub Tulakan, and sub Tegal Ombo, and case studies as an approach to research, this study is very important because policy makers rural development can not ignore the existence of energy this social in an effort to empower communities for rural development.